Blinde vinkler. Billeder af kolonien Dansk Vestindien - Meyer, Mette Kia Krabbe; Giersing, Sarah; Danbolt, Mathias (Magasin fra Det Kongelige Bibliotek, 2017)
<span style="line-height: 120%; font-family: ’Verdana’,sans-serif; font-size: 7.5pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: DA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Tale ved åbning af udstillingen 18. maj 2017